Performance Study of Glassfibre Reinforced Concrete (GRC) with Ferric Oxide Waste Additive - Vivin Setiani; Wiwik Dwi Pratiwi; Denny Dermawan; Luqman Cahyono; Mohamad Hakam; Ryan Yudha Adhitya; Mochammad Karim Al Amin; Nur Fajar Aprilia Sari; Wanda Cahyaning Ati; Lina Indawati (Universitas Diponegoro, 2026)
Portland cement production is a major contributor to carbon emissions in the construction sector because the high-temperature calcination process produces CO₂ emissions that are nearly equivalent to the mass of cement produced. This study focuses on evaluating the potential of ferric oxide waste material in glass fiber-reinforced concrete as a filler to reduce carbon emissions, making it more environmentally friendly. An experimental method was used with a 1:1 binder-to-aggregate ratio and a constant 3% glass fiber addition. The percentage of ferric oxide replacement in the cement was 0–40%. X-ray fluorescence, X-ray diffraction, particle size distribution analysis, sand gradation testing, and mud content were used to obtain the material data. Tests were also conducted to determine compressive strength, flexural strength, water absorption, and dry and wet bulk density. Based on the results obtained, the addition of ferric oxide improved the mechanical properties of glass fiber-reinforced concrete and added to the aesthetic value of the final product. These findings indicate that the application of Glassfibre Reinforced Concrete is environmentally friendly